Induction of protective immunity against Chlamydia muridarum intracervical infection in DBA/1j mice - Tang, Lingli (2013)
We previously reported that intracervical inoculation with Chlamydia muridarum induced hydrosalpinx in DBA/1j mice, but intravaginal inoculation failed to do so. In the current study, we found unexpectedly that intrabursal inoculation of live chlamydial organisms via the oviduct failed to induce significant hydrosalpinx. We further tested whether primary infection via intravaginal or intrabursal inoculation could induce protective immunity against hydrosalpinx following intracervical challenge infection. Mice infected intravaginally with C. muridarum were fully protected from developing hydrosalpinx, while intrabursal inoculation offered partial protection. We then compared immune responses induced by the two genital tract inoculations. Both inoculations induced high IFNγ and IL-17 T cell responses although the ratio of IgG2a versus IgG1 in intravaginally infected mice was significantly higher than in mice infected intrabursally. When the antigen-specificities of antibody responses were compared, both groups of mice dominantly recognized 24 C. muridarum antigens, while each group preferentially recognized unique sets of antigens. Thus, we have demonstrated that intrabursal inoculation is neither effective for causing hydrosalpinx nor efficient in inducing protective immunity in DBA/1j mice. Intravaginal immunization, in combination with intracervical challenge infection in DBA/1j mice, can be a useful model for understanding mechanisms of chlamydial pathogenicity and protective immunity.